Testicular Plasmablastic Lymphoma in an HIV-Negative Patient: A Rare Case Presentation - Kemnasom Nwanwene MD; Noman Ahmed Jang Khan MD; Mohamed Alsharedi MD (SAGE Publishing, 2021)
Plasmablastic lymphoma (PBL) is a very rare disease and it is usually considered a human immunodeficiency virus (HIV)-related B-cell lymphoma that carries a poor prognosis. It mostly involves the oral cavity, lungs, nasal cavity, gastrointestinal tract, lymph node, and skin. Therapeutic regimens like dose-adjusted etoposide, vincristine, doxorubicin, cyclophosphamide, and prednisone (DA-EPOCH) have shown better results in these aggressive lymphomas. We report a rare case of PBL in an HIV-negative patient who presented to the clinic with a complaint of left testicular swelling for 3 months. Ultrasound showed an enlarged left testicle. He underwent a left orchiectomy and the pathology showed PBL with involvement of the spermatic cord margin. Positron emission tomography scan showed hypermetabolic mediastinal and hilar lymph nodes. He was started on DA-EPOCH but showed no response. Accordingly, salvage therapy with bortezomib in addition to ifosfamide carboplatin and etoposide (B-ICE) chemotherapy was initiated with remarkable response. Several other regimens can be used in the refractory setting; however, the evidence is mostly based on retrospective analysis.